10 tháng 11 lúc 18:43

Bài 5:

1) $2\sqrt{3x}-4\sqrt{3x}-3\sqrt{3x}=-30\left(x\ge0\right)$

$\Leftrightarrow\sqrt{3x}\left(2-4-3\right)=-30$

$\Leftrightarrow-5\sqrt{3x}=-30$

$\Leftrightarrow\sqrt{3x}=6$

$\Leftrightarrow3x=36$

$\Leftrightarrow x=12\left(tm\right)$

2) $3\sqrt{2x}-5\sqrt{8x}+7\sqrt{18x}=28\left(x\ge0\right)$

$\Leftrightarrow3\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}=28$

$\Leftrightarrow14\sqrt{2x}=28$

$\Leftrightarrow\sqrt{2x}=2$

$\Leftrightarrow2x=4$

$\Leftrightarrow x=2\left(tm\right)$

3) $5\sqrt{12x}-4\sqrt{3x}+2\sqrt{48x}=14\left(x\ge0\right)$

$\Leftrightarrow10\sqrt{3x}-4\sqrt{3x}+8\sqrt{3x}=14$

$\Leftrightarrow14\sqrt{3x}=14$

$\Leftrightarrow\sqrt{3x}=1$

$\Leftrightarrow3x=1$

$\Leftrightarrow x=\dfrac{1}{3}\left(tm\right)$

4) $\sqrt{4x-20}+\sqrt{x-5}-\dfrac{1}{3}\sqrt{9x-45}=4\left(x\ge5\right)$

$\Leftrightarrow\sqrt{4\left(x-5\right)}+\sqrt{x-5}-\dfrac{1}{3}\cdot3\sqrt{x-5}=4$

$\Leftrightarrow2\sqrt{x-5}+\sqrt{x-5}-\sqrt{x-5}=4$

$\Leftrightarrow2\sqrt{x-5}=4$

$\Leftrightarrow\sqrt{x-5}=2$

$\Leftrightarrow x-5=4$

$\Leftrightarrow x=9\left(tm\right)$

Bình luận (1)
10 tháng 11 lúc 18:36

help

Bình luận (0)
10 tháng 11 lúc 20:11

5: ĐKXĐ: x>=1/2

$\sqrt{2x-1}=\sqrt{2}-1$

=>$2x-1=\left(\sqrt{2}-1\right)^2=3-2\sqrt{2}$

=>$2x=3-2\sqrt{2}+1=4-2\sqrt{2}$

=>$x=2-\sqrt{2}$(nhận)

6: ĐKXĐ: x>=-5

$\sqrt{x+5}=\sqrt{3}-2$

mà $\sqrt{3}-2=\sqrt{3}-\sqrt{4}< 0$

nên phương trình vô nghiệm

7:

ĐKXĐ: x>=-11/3

$\sqrt{3x+11}=3+\sqrt{2}$

=>$3x+11=\left(3+\sqrt{2}\right)^2=11+6\sqrt{2}$

=>$3x=6\sqrt{2}$

=>$x=2\sqrt{2}\left(nhận\right)$

8: ĐKXĐ: x>=-38

$\sqrt{x+38}=3+\sqrt{5}$

=>$x+38=\left(3+\sqrt{5}\right)^2=14+6\sqrt{5}$

=>$x=14+6\sqrt{5}-38=-24+6\sqrt{5}$(nhận)

9: ĐKXĐ: x>=-5

$\sqrt{4x+20}-3\sqrt{x+5}-\dfrac{4}{3}\cdot\sqrt[2]{9x+45}=6$

=>$2\sqrt{x+5}-3\sqrt{x+5}-\dfrac{4}{3}\cdot3\sqrt{x+5}=6$

=>$-5\sqrt{x+5}=6$(vô lý)

=>Phương trình vô nghiệm

10: ĐKXĐ: x>=1

$\sqrt{25x-25}-\dfrac{15}{2}\cdot\sqrt{\dfrac{x-1}{9}}=6+\sqrt{x-1}$

=>$5\sqrt{x-1}-\dfrac{15}{2}\cdot\dfrac{\sqrt{x-1}}{3}-\sqrt{x-1}=6$

=>$\dfrac{3}{2}\cdot\sqrt{x-1}=6$

=>$\sqrt{x-1}=4$

=>x-1=16

=>x=17(nhận)

11: ĐKXĐ: x>=0

$\dfrac{3\sqrt{x}-5}{2}-\dfrac{2\sqrt{x}-7}{3}=\sqrt{x}-1$

=>$\dfrac{3\left(3\sqrt{x}-5\right)-2\left(2\sqrt{x}-7\right)}{6}=\sqrt{x}-1$

=>$9\sqrt{x}-15-4\sqrt{x}+14=6\left(\sqrt{x}-1\right)=6\sqrt{x}-6$

=>$5\sqrt{x}-1=6\sqrt{x}-6$

=>$-\sqrt{x}=-5$

=>$\sqrt{x}=5$

=>x=25(nhận)

Bình luận (0)

Các câu hỏi tương tự
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết